USING MODERN INFORMATION TECHNOLOGIES IN PUBLISHING (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The article discusses the use of modern information technologies in the publishing process. It covers the development of computer systems in publishing, including the automation of processes for creating, editing, and publishing text and graphic materials. Special emphasis is placed on the role of Desktop Publishing (DTP) systems in increasing the efficiency of the publishing process. The article analyzes the integration of information technologies into publishing processes and their impact on improving modern printing processes. Innovations in the printing process and publication creation are also discussed.